2009
DOI: 10.1016/j.neuropharm.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glycogen synthase kinase-3 activity in Fragile X mice: Key metabolic regulator with evidence for treatment potential

Abstract: a b s t r a c tSignificant advances have been made in understanding the underlying defects of and developing potential treatments for Fragile X syndrome (FXS), the most common heritable mental retardation. It has been shown that neuronal metabotropic glutamate receptor 5 (mGluR5)-mediated signaling is affected in FX animal models, with consequent alterations in activity-dependent protein translation and synaptic spine functionality. We demonstrate here that a central metabolic regulatory enzyme, glycogen synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
187
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(205 citation statements)
references
References 88 publications
17
187
1
Order By: Relevance
“…Finally, we found that the rescuing effect of MPEP and GSK inhibitors is quite similar regardless of electrophysiological, behavioral, or biochemical phenotypes, suggesting that mGluR5 and GSK3 may link to each other. Previous studies found that MPEP inhibits GSK3 activity by increasing the inhibitory phosphorylation of GSK3 (Liu et al, 2005;Min et al, 2009;Yuskaitis et al, 2010), whereas combined inhibition of mGluR5 and GSK3 does not cause synergistic effect (Min et al, 2009). Therefore, it is likely that GSK3 is one of the downstream targets of mGluR5.…”
Section: Pharmacological Inhibition Of Mglur5 or Gsk3mentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, we found that the rescuing effect of MPEP and GSK inhibitors is quite similar regardless of electrophysiological, behavioral, or biochemical phenotypes, suggesting that mGluR5 and GSK3 may link to each other. Previous studies found that MPEP inhibits GSK3 activity by increasing the inhibitory phosphorylation of GSK3 (Liu et al, 2005;Min et al, 2009;Yuskaitis et al, 2010), whereas combined inhibition of mGluR5 and GSK3 does not cause synergistic effect (Min et al, 2009). Therefore, it is likely that GSK3 is one of the downstream targets of mGluR5.…”
Section: Pharmacological Inhibition Of Mglur5 or Gsk3mentioning
confidence: 97%
“…We thus tested whether mGluR5 antagonist MPEP could rescue the deficient L-LTP and network recruitment observed in ACC slices of Fmr1 KO mice. Furthermore, GSK3 functions closely to mGluR5 signaling, and excessive expression of GSK3 in cortex has been reported in Fmr1 KO mice (Berry-Kravis et al, 2008; Min et al, 2009). We also tested whether inhibition of GSK3 could rescue L-LTP and network recruitment.…”
Section: Pharmaceutical Rescuing Of L-ltp and Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this mGluR hypothesis of Fragile X Syndrome, analysis of double KO Drosophila of dFmr1 (homolog of the human FMR1 gene) and dmGluRA (the Drosophila mGluR) has suggested that these two genes converge to regulate postsynaptic GluR trafficking, synaptic ultrastructure and plasticity, and motor behavior [57][58][59]. 2-methyl-6-(phenylethynyl)-pyridine (MPEP), a potent negative modulator of mGluR5 [60], consistently rescues many FXSrelated deficits in KO mice [50,55,56,[61][62][63], fly [64][65][66] and zebrafish [67], implying the therapeutic potential of FXS using mGluR5 inhibitors. Indeed, multiple human clinical trials with chemicals targeting mGluR5, or mGluRs-related signaling pathways, or presynaptic release of glutamate, such as gamma-aminobutyric acid (GABA) B receptor agonists, are being conducted, and are showing promising, but as yet inconclusive, results with regard to treating FXS [68][69][70][71].…”
Section: Fragile X Mental Retardationmentioning
confidence: 98%
“…FMR1-deficient mice show increased locomotor activity in the open-field test, elevated anxiety levels in the mirror-chamber test, and impaired social interaction with unfamiliar partners in multiple tests [52][53][54][55][56]. Interestingly, the FXS-like behavior phenotypes in FMR1 KO mice were rescued by repressing the function of group 1 metabotropic glutamate receptors (Gp1 mGluRs).…”
Section: Fragile X Mental Retardationmentioning
confidence: 99%